Storage characteristics evaluation of late-maturing Actinidia arguta resources pollinated by different male pollens - Qinjia Zhao; Lin Hui; Huanyu Wang; Miao Yan; Guanlin Qian; Heran Xu; Naizhu Liu; Guang Xin; Song Pan (Postharvest Biology and Technology, 2027)

New perspectives on the role of oil-gas in mineralization of sandstone-hosted uranium deposits: Carbonate evidence from Yuejin Ⅱ, Qaidam Basin, China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Jun-Ying Ding; Zhi-Lin Cheng; Zhao-Hui Li; Xue-Feng Gao; Ping Feng (Journal of Asian Earth Sciences, 2026)

PFAS exposure is associated with retinal neurotoxicity in Chinese adolescents: Mechanistic insights from integrated toxicogenomic and in vitro analyses - Xing-Xuan Dong; Shi-Yi Gong; Yu-Hui Hu; Gang Liang; Hua Xu; Dan-Lin Li; Yun Zhao; Chen-Wei Pan (Environmental Pollution, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

Genome-wide association analysis for resistance against iridovirus disease in large yellow croaker (Larimichthys crocea) from a natural outbreak population - Ying Pan; Hongshu Chi; Nengfeng Lin; Junjia Zeng; Xiaodong Liu; Xiuxia Chen; Zaiyu Zheng; Qiuhuan Jiang; Xunkai Yu; Hui Gong (Fish & Shellfish Immunology, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Deciphering multi-stage W-Sn mineralization at ore-field scale: new U-Pb geochronology and trace element fingerprinting from the world-class Dayu district, Nanling - Kai-Han Zhang; Pei Ni; Jun-Yi Pan; Yao-Hui Jiang; Guo-Guang Wang; Ming-Sen Fan; Gen-Wen He; Lin-Lin Peng; Zhe Chi; Liang Han; Jun-Ying Ding; Wen-Sheng Li (International Geology Review, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Distinction in Symbiodiniaceae and Bacterial Communities and Symbiodiniaceae Lineage‐Specific Transcriptome Underpinning the Superior Heat Tolerance of Intertidal Acropora Corals - Pan Zhang; Lin‐Tao Huang; Xiao‐Lei Yu; Yu‐Yang Zhang; Sheng Liu; Lei Jiang; Hui Huang (Molecular Ecology, 2026)
Fine‐scale thermal heterogeneity within intertidal and subtidal microhabitats could drive divergence in organismal heat tolerance. Reef corals from the extreme intertidal may hold optimism for the future of coral reefs and give insights into the mechanisms by which coral may persist under future conditions. Here, we compared the thermal sensitivities of intertidal and subtidal Acropora digitifera and evaluated their bleaching phenotypes, transcriptomes, host genetic differentiation and bacterial communities. Results showed that only heat‐exposed subtidal corals displayed significantly reduced photochemical efficiency, symbiont densities, pigment and host protein concentrations, suggesting bleaching and host starvation. Despite being genetically similar, heat‐exposed subtidal corals mounted stronger immune activation and amino acid degradation but downregulated monocarboxylate transport and calcification compared to intertidal corals. In contrast to the prevalence of Cladocopium in subtidal corals, intertidal corals were dominated by Durusdinium , whose transcriptional signature was characterised by lineage‐specific and constitutively high transcript abundance of orthologs involved in stress response, metabolism, photosynthesis, cell cycle and symbiotic interactions. Furthermore, 16S rRNA sequencing demonstrated an origin‐dependent bacterial composition, with Endozoicomonas being more abundant and important in co‐occurrence networks of intertidal corals. Our findings suggest that distinction in Symbiodiniaceae and bacterial communities and Symbiodiniaceae lineage‐specific transcriptional footprint largely underpin the exceptional thermotolerance of intertidal Acropora . Although these corals provide promising avenues for restoration, such a mechanism may bring attention to the risk of using them in selective breeding, particularly given the horizontal transmission of algal symbionts in Acropora .

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

An Introduction to the Synthesis Community Integrated Model Version 2 (SYCIM2.0) and Its Simulation of the East Asian Summer Monsoon - Wenjun Liang; Wenjie Dong; Danya Xu; Bin Wang; Li Liu; Yanli Tang; Jie Yang; Song Wang; Fuhai Dao; Duofan Zheng; Chenhao Li; Fei Liu; et al. (Advances in Atmospheric Sciences, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Drying-rewetting legacy mitigates freezing-thawing effects on soil microbial communities and greenhouse gas emissions in plateau riparian wetlands - Lin Ma; Yongtai Pan; Hui Liu; Guihua Liu; Wenzhi Liu (Environmental Pollution, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Interactive effects of warming and drought on soil organic carbon sequestration and methane uptake in straw and biochar amended soils: Mechanisms and global implications - Jitong Lin; Guopeng Liang; Marcela Hernández; Zhiyu Xu; Yinghao Xue; Renhua Sun; Yuanfeng Sun; Lulu Dai; Yanhong Lou; Haojie Feng; Hui Wang; Quangang Yang; et al. (Chemical Engineering Journal, 2025)

Terpene and lignan glycosides from the leaves of Cyclocarya paliurus and their anti-inflammatory activity - Si-Yang Fang; Jia Liu; Chang-Jian Wu; Xing-Gui Zhang; Hui-Lin Dong; Dong-Jian Zhang; Can Hu; Jian Zhang; Ke Pan; Zhi-Qi Yin; Yan-Hua Qin; Lei Wang (Phytochemistry, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Nano Sim@ZIF8@PDA modified injectable temperature sensitive nanocomposite hydrogel for photothermal/drug therapy for peri-implantitis - Dingkun Liu; Jinbing Chen; Linjuan Gao; Xing Chen; Liujun Lin; Yuan Liu; Xia Wei; Yu Pan; Yinghui Wang; Hui Cheng (Carbohydrate Polymers, 2025)

Landscape Stability Assessment and Simulation Analysis Under Urban Expansion: A Case Study of Hangzhou, China - Hui Pei; Lin Zhang; Minli Zhou; Wenbin Nie; Shihao Zhou; Yan Shi; Jianyun Pan (Chinese Geographical Science, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Neutrophil Membrane Nanovesicles Alleviate the Renal Function Indicators in Acute Kidney Injury Caused by Septic Rats - Junhao Pan; Feifei Shao; Xiaorong Xiao; Xin Ke; Zhihui Guan; Hui Lin; Qingqing Yan; Xinyao Xiang; Jinming Luo (Cell Biochemistry and Biophysics, 2025)

Enhancing porcine oocyte quality and embryo development through natural antioxidants - Zheng Feng; Jia Song; Chenghong Lin; Siyu Wu; Yu Wang; Qingyuan Hui; Yinting Pan; Yiman Zou; Chaofeng Zeng; Jinbiao Guo; Yangli Pei (Theriogenology, 2025)

Microbial groups containing alkaline phosphatase accelerate soil phosphate mineralization in two soil patterns with contrasting pH levels - Hui Li; Jitong Lin; Qi Shao; Beibei Zhang; Yunting Wang; Linke Wang; Haojie Feng; Yanhong Lou; Hui Wang; Quangang Yang; Zhongchen Yang; Hongjie Di; et al. (Journal of Soils and Sediments, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Enhancing arsenate removal through interpretable machine learning guiding the modular design of metal–organic frameworks - Zuhong Lin; Hui Cai; Hongjia Peng; Ying Fang; Pengxu Pan; Haipu Li; Ying Yang; Jingjing Yao (Chemical Engineering Journal, 2024)

Local adaptation of trophic strategy determined the tolerance of coral Galaxea fascicularis to environmental fluctuations - Xiao-Lei Yu; Cheng-Yue Liu; Lei Jiang; Lin-Tao Huang; Yong Luo; Pan Zhang; Yu-Yang Zhang; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

Downregulation of OATP2B1 by proinflammatory cytokines leads to 5-ASA hyposensitivity in Ulcerative colitis - Ping Li; Jun Luo; Yiming Jiang; Xiaoyi Pan; Minlei Dong; Binxin Chen; Jinhai Wang; Hui Zhou; Huidi Jiang; Yangri Duan; Nengming Lin (Chemico-Biological Interactions, 2024)

Soat2 inhibitor avasimibe alleviates acute pancreatitis by suppressing acinar cell ferroptosis - Weiwei Luo; Lin Chen; Hui Sun; Siqin Zhang; Xiaowu Dong; Jiajia Pan; Weiming Xiao; Guotao Lu; Yaodong Wang; Hongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Life-stage specificity and temporal variations in transcriptomes and DNA methylomes of the reef coral Pocillopora damicornis in response to thermal acclimation - Lei Jiang; Pan Zhang; Lin-Tao Huang; Xiao-Lei Yu; Cheng-Yue Liu; Xiang-Cheng Yuan; Sheng Liu; Hui Huang (Science of The Total Environment, 2024)

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

Enhanced peroxymonosulfate activation via MOF-derived bimetal core-shell Co-Fe@NC hybrids to degrade emerging pollutants - Hui Li; Xinlei Ren; Wenxue Pan; Shiting Zhu; Jin Zhang; Zhiyuan Yang; Liu Qian; Yueying Wang; Yujing Huang; Lin Guo; Minghui Xiang (Journal of Environmental Chemical Engineering, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

Cryopreservation of Goldlined seabream Rhabdosargus sarba (Forsskål, 1775) sperm: CASA observation and enzyme activity evaluation - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Aquaculture, 2024)

Synergistic effect of donor-acceptor structure and built-in electric field in hollow-spherical carbon nitride homojunction towards effective charge transfer and excellent photocatalytic hydrogen evolution performance - Runlu Liu; Jingyi Lin; Lulu Zhu; Xiaoxiao Zhang; Yao Li; Hui Pan; Lingti Kong; Shenmin Zhu; John Wang (Chemical Engineering Journal, 2024)

Effects of flue gas desulfurization gypsum and clover planting on qualities of soil and winter jujube in coastal saline-alkali orchard of north China - Qi Shao; Xuejing Xia; Guihua Li; Hui Li; Jitong Lin; Yanhong Lou; Quangang Yang; Hui Wang; Zhongchen Yang; Hong Pan; Yuping Zhuge (Soil Ecology Letters, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Evaluation storage capacity of six kind late-maturing Actinidia arguta resources - Jiabao Wang; Guanlin Qian; Song Pan; Tiancheng Ye; Miao Yan; Xiaoman Liang; Lin Hui; Xina Cong; Ruiyu Yang; Heran Xu; Guang Xin (Journal of Stored Products Research, 2023)

HLEL: A wetland classification algorithm with self-learning capability, taking the Sanjiang Nature Reserve I as an example - Wenhan Jiang; Meng Zhang; Jiangping Long; Yulin Pan; Yimin Ma; Hui Lin (Journal of Hydrology, 2023)

Immunomodulatory effect of earthworm protein autolysates on Cyclophosphamide(CTX)-Induced immunosuppressed mice - Yizhe Zhang; Ping He; Leiman Pan; Zhengli Lin; Jinxi Yang; Hui Wu; Mengmeng Zhang (Food Bioscience, 2023)

Role of feeding and physiological trade-offs in sustaining resilience of the coral Galaxea fascicularis to light limitation - Xiao-Lei Yu; Lei Jiang; Yong Luo; Cheng-Yue Liu; Yu-Yang Zhang; Lin-Tao Huang; Pan Zhang; Xiang-Cheng Yuan; Hui Huang (Coral Reefs, 2023)

Assessment of microplastic contamination in an eastern Pacific tuna (Katsuwonus pelamis) and evaluation of its health risk implication through molecular docking and metabolomics studies - Lijun Wu; Xiaojie Dai; Jing Xu; Danyun Ou; Lei Wang; Hui Lin; Weiyi He; Haitao Lin; Rupeng Du; Hao Huang; Weiwen Li; Zhong Pan (Food Chemistry, 2023)

Cryopreservation of black seabream (Acanthopagrus schlegelii) sperm - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Theriogenology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Prussian blue analogues derived magnetic FeCo@GC material as high-performance metallic peroxymonosulfate activators to degrade tetrabromobisphenol A over a wide pH range - Liu Qian; Hui Li; Dengsong Zhang; Lin Guo; Wenxue Pan; Jin Zhang; Minghui Xiang (Environmental Science and Pollution Research, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Diagenetic effect on barium isotope compositions of barites in the lower Cambrian successions - Lan-Lan Tian; Wei Wei; Lin-Hui Dong; Songqi Pan; Zhenhua Jing; Fang Huang (Chemical Geology, 2023)

Influence of Rice Straw Biochar Application on Soil Nutrient Dynamics and Rice Productivity Under Different Irrigation Regimes - Le Chen; Lin Guo; Xueyun Deng; Xiaohua Pan; Xiaobing Xie; Xueming Tan; Ping Liao; Qiangqiang Xiong; Qigen Dai; Hui Gao; Haiyan Wei; Yongjun Zeng; et al. (Journal of Soil Science and Plant Nutrition, 2023)

DNA methylation age acceleration contributes to the development and prediction of non-alcoholic fatty liver disease - Mingfeng Xia; Wenran Li; Huandong Lin; Hailuan Zeng; Shuai Ma; Qi Wu; Hui Ma; Xiaoming Li; Baishen Pan; Jian Gao; Yu Hu; Yun Liu; et al. (GeroScience, 2023)
Non-alcoholic fatty liver disease (NAFLD) is prevalent in the aging society. Despite body weight reduction, the prevalence of NAFLD has been increasing with aging for unknown reasons. Here, we investigate the association of DNA methylation age acceleration, a hallmark of aging, with risk of NAFLD. Genome-wide DNA methylation profiles were measured in 95 participants who developed type 2 diabetes during 4-year follow-up, and 356 randomly sampled participants from Shanghai Changfeng Study. DNA methylation age was calculated using the Horvath’s method, and liver fat content (LFC) was measured using a quantitative ultrasound method. Subjects with highest tertile of DNA methylation age acceleration (≥ 9.5 years) had significantly higher LFC (7.2% vs 3.1%, P = 0.008) but lower body fat percentage (29.7% vs 33.0%, P = 0.032) than those with lowest tertile of DNA methylation age acceleration (< 4.0 years). After adjustment for age, sex, alcohol drinking, cigarette smoking, BMI, waist circumference, and different type blood cell counts, the risk of NAFLD was still significantly increased in the highest tertile group (OR, 4.55; 95% CI, 1.06–19.61). Even in subjects with similar LFC at baseline, DNA methylation age acceleration was associated with higher increase in LFC (4.0 ± 10.7% vs 0.9 ± 9.5%, P = 0.004) after a median of 4-year follow-up. Further analysis found that 6 CpGs of Horvath age predictors were associated with longitudinal changes in LFC after multivariate adjustment and located on genes that might lead to fat redistribution from peripheral adipose to liver. Combination of the key CpG methylation related to liver fat content with conventional risk factors improves the performance for NAFLD prediction. Graphical Abstract

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

Reinforced human intervention drives microplastic pollution in estuarine beaches and nearshore sediments of Dongshan Bay, China - Zhong Pan; Qianlong Liu; Rupeng Du; Weiwen Li; Hui Lin (Gondwana Research, 2023)

Hydrogen sulfide antagonizes formaldehyde-induced ferroptosis via preventing ferritinophagy by upregulation of GDF11 in HT22 cells - Yu-Hui Tang; Lei Wu; Hong-Lin Huang; Pan-Pan Zhang; Wei Zou; Xiao-Qing Tang; Yi-Yun Tang (Toxicology, 2023)

Microplastics may act as a vector for potentially hazardous metals in rural soils in Xiamen, China - Rupeng Du; Yufang Wu; Haitao Lin; Jincheng Sun; Weiwen Li; Zhong Pan; Shaojian Zeng; Qi Chen; Jinjing Luo; Hui Lin (Journal of Soils and Sediments, 2023)

Machine learning-based mRNA signature in early acute myocardial infarction patients: the perspective toward immunological, predictive, and personalized - Hai-Hua Pan; Na Yuan; Ling-Yan He; Jia-Lin Sheng; Hui-Lin Hu; Chang-Lin Zhai (Functional & Integrative Genomics, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

Screening, ACE-inhibitory mechanism and structure-activity relationship of a novel ACE-inhibitory peptide from Lepidium meyenii (Maca) protein hydrolysate - Zhengli Lin; Junwen Lai; Ping He; Leiman Pan; Yizhe Zhang; Mengmeng Zhang; Hui Wu (Food Bioscience, 2023)

Experimental and numerical simulation study on thermal decomposition model of ammonium nitrate - Lin-Quan Gong; Jia-Jia Jiang; Jun-hui Gong; Yong Pan; Jun-Cheng Jiang (Process Safety and Environmental Protection, 2023)

Residue screening and analysis of enrofloxacin and its metabolites in real aquatic products based on ultrahigh-performance liquid chromatography coupled with high resolution mass spectrometry - Jinxia Dai; Ye Wang; Hui Lin; Yanmin Sun; Yuning Pan; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Determination of chlorpromazine and its metabolites in animal-derived foods using QuEChERS-based extraction, EMR-Lipid cleanup, and UHPLC-Q-Orbitrap MS analysis - Jinxia Dai; Hui Lin; Yuning Pan; Yanmin Sun; Ye Wang; Jun-qin Qiao; Hong-zhen Lian; Chun-xiang Xu (Food Chemistry, 2023)

Genome-wide association study reveals markers and candidate genes associated with growth in the rice flower carp, an economic fish species of integrated rice-fish culture in China - Hui Luo; Xianhui Pan; Yin Huang; Zhe Li; Hua Ye; Kangqi Zhou; Luting Wen; Junqi Qin; Wenping He; Xuesong Du; Dapeng Wang; Yong Lin (Frontiers in Marine Science, 2023)
The rice flower carp ( Cyprinus carpio ) is an important fish in integrated rice-fishery farming. Here, we performed the first genome-wide association study (GWAS) for seven growth traits (including body mass, total length, body length, body height, body width, caudal-peduncle depth, and eye spacing) in 200 rice flower carp samples using 369,688 high-quality SNPs and 42,225 indels obtained by double-digest genotyping-by-sequencing (ddGBS). The morphometrics of these traits were highly correlated (Pearson’s correlation coefficients = 0.74–0.99, p < 0.001). GWAS detected 15, 5, 4, 26, 7, 16, and 17 loci significant associated (-log10P ≥ 5) with body mass, total length, body length, body width, body height, caudal-peduncle depth, and eye spacing, respectively. Subsequently, within the 50 kb upstream and downstream regions surrounding these significant loci, 38, 19, 18, 20, 52, 27, and 37 candidate genes for the seven growth traits were detected, respectively. Importantly, B6_4352672 and A8_4978825 were significantly associated with more than five growth traits. These results showed loci significantly associated with more than five growth traits will be helpful for future marker-assisted selection (MAS). Interestingly, chromosomes A8 and B25 had many loci significantly associated with growth traits, most of which were shared among multiple growth-related traits. These results indicated that chromosome A8 and B25 may be closely related to growth traits. Our findings not only help understand the genetic architecture of growth traits in fish but facilitate the identification of candidate genes for marker-assisted selection towards breeding faster-growing rice flower carp in the future.

Microplastic pollution threats coastal resilience and sustainability in Xiamen City, China - Jincheng Sun; Yongqiang Tian; Shuanxi Liu; Haitao Lin; Rupeng Du; Hui Lin; Zhong Pan; Zhisong Zhang; Wenfeng Xu (Marine Pollution Bulletin, 2023)

Transboundary microplastic pollution in Xiamen Bay and adjacent Jiulong River estuary after the outbreak of COVID-19 - Haitao Lin; Huanglei Pan; Jincheng Sun; Rupeng Du; Jielong Xu; Hui Lin; Zhong Pan; Mazhan Zhuang (Science of The Total Environment, 2023)

Construction of 1D/0D CdS nanorods/Ti3C2 QDs Schottky heterojunctions for efficient photocatalysis - Chengqun Xu; Dezhi Li; Haiyang Liu; Dongyu Wang; Xiaolu Liu; Shiyin Lin; Yuchen Yang; Donghua Fan; Hui Pan (Journal of Environmental Chemical Engineering, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Vanadium isotope evidence for widespread marine oxygenation from the late Ediacaran to early Cambrian - Wei Wei; Xi Chen; Hong-Fei Ling; Fei Wu; Lin-Hui Dong; Songqi Pan; Zhenhua Jing; Fang Huang (Earth and Planetary Science Letters, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Rice straw biochar reduces Cd accumulation and promotes Cu accumulation in rice: irrigation regime is the driving factor - Le Chen; Lin Guo; Ping Liao; Qiangqiang Xiong; Xueyun Deng; Hui Gao; Haiyan Wei; Qigen Dai; Xiaohua Pan; Yongjun Zeng; Hongcheng Zhang (Journal of Soils and Sediments, 2023)

An automated, fully-integrated nucleic acid analyzer based on microfluidic liquid handling robot technique - Tong-Tong Lin; Jian-Wei Wang; Qian-Nuan Shi; Hui-Feng Wang; Jian-Zhang Pan; Qun Fang (Analytica Chimica Acta, 2023)

N2O emissions from soils under short-term straw return in a wheat-corn rotation system are associated with changes in the abundance of functional microbes - Jitong Lin; Zhiyu Xu; Yinghao Xue; Renhua Sun; Rongguang Yang; Xiaoxu Cao; Hui Li; Qi Shao; Yanhong Lou; Hui Wang; Quangang Yang; Hong Pan; et al. (Agriculture, Ecosystems & Environment, 2023)

Breast cancer incidence in a national cohort of female workers exposed to special health hazards in Taiwan: a retrospective case-cohort study of ~ 300,000 occupational records spanning 20 years - Yun-Shiuan Chuang; Chun-Ying Lee; Pei-Chen Lin; Chih-Hong Pan; Hui-Min Hsieh; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

The particle fluxes in sediment traps from Niulang Guyot area in the Northwest Pacific Ocean - Xiuwu Sun; Jinmin Chen; Baohong Chen; Cai Lin; Yang Liu; Jiang Huang; Zhong Pan; Kaiwen Zhou; Qing He; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Plant secondary metabolite and temperature determine the prevalence of Arsenophonus endosymbionts in aphid populations - Chun‐Yan Chang; Xiao‐Wan Sun; Pan‐Pan Tian; Ning‐Hui Miao; Yu‐Lin Zhang; Xiang‐Dong Liu (Environmental Microbiology, 2022)
Summary Transmission rate and role in hosts contribute to the prevalence of an endosymbiont. However, factors affecting transmission and role of facultative endosymbionts are still not well understood. Here, we illustrated that host plants and environmental temperatures affected the transmission, relative abundance and role of Arsenophonus in the cotton aphid Aphis gossypii . The transmission rate of this endosymbiont from mother aphids to offspring was relatively lower. High temperatures impeded the transmission, and infection rates declined as aphids were exposed to 30°C. Contents of amino acids and secondary metabolites were remarkably different among host plants. Aphids feeding on zucchini leaves containing a higher titre of amino acids and lower secondary metabolites harboured a relatively lower abundance of Arsenophonus . Concentrations of an amino acid and a plant secondary metabolite, cucurbitacin B, in aphid diet were not associated with Arsenophonus abundance. However, gossypol, another plant secondary metabolite, was strongly related with the abundance. Arsenophonus imparted a fitness benefit to aphids, and the benefit was dependent on host plants and gossypol concentration. In sum, plant secondary metabolite and environmental temperature affect transmission, relative abundance and role of Arsenophonus , which determine the endosymbiont prevalence in aphid populations.

Seasonal Distributions of Methane in a Populous Urban Coastal Sea Area - Hsiao-Chun Tseng; Chia-Chia Lin; Hui-Juan Pan; Yokie Tai Yuh Han; Gwo-Ching Gong (Frontiers in Marine Science, 2022)
Methane (CH 4 ) is an important greenhouse gas, and its concentrations in aquatic areas are heavily influenced by anthropogenic activities, especially human-induced eutrophication, polluted river discharge and wastewater treatment plant (WWTP) effluents. Although coastal areas and estuaries contribute large amounts of global oceanic CH 4 emissions, the relative contributions of different sources have not been well determined. The Tamsui River located in northern Taiwan is an urban river flowing through populated cities and thus likely carries large amounts of contaminants, such as nutrients and organic matter to the estuary. In this study, we characterized the spatial distribution and seasonal variations in CH 4 in the Tamsui River estuary adjacent marine areas. The sea-to-air CH 4 fluxes were also estimated to quantify the strength of the study area as an atmospheric CH 4 source. Our results showed that CH 4 concentrations in coastal sea areas were influenced by WWTP effluents, sediment and freshwater inputs. Thus, river discharge and nutrient levels as well as strong vertical mixing and disturbances might increase CH 4 concentrations and emissions. The seasonal surface CH 4 concentrations and sea-to-air CH 4 fluxes were 13.7 ± 18.7 nM and 41.7 ± 68.0 μmol m -2 d -1 in autumn; 29.3 ± 19.8 nM and 61.3 ± 44.6 μmol m -2 d -1 in spring; 21.8 ± 13.9 nM and 37.0 ± 26.2 μmol m -2 d -1 in summer; and 27.0 ± 21.4 nM and 85.9 ± 75.4 μmol m -2 d -1 in winter.

Changes in the growth performance, antioxidant enzymes and stress resistance caused by dietary administration of synbiotic (fructooligosaccharide and probiotics) in juvenile Chinese Mitten Crab, Eriocheir sinensis - Jin-Juan Wan; Jian-lin Pan; Mei-Fang Shen; Hui Xue; Meng-lin Sun; Mei-Qin Zhang; Xi-He Zhu; Xing-kong Ma (Aquaculture International, 2022)

Molecular Identification of Species Diversity Using Pelagic Fish Eggs in Spring and Late Autumn-Winter in the Eastern Beibu Gulf, China - Gang Hou; Yanying Chen; Jinrun Wang; Chuanhao Pan; Jianbin Lin; Bo Feng; Hui Zhang (Frontiers in Marine Science, 2022)
The Beibu Gulf is considered as one of China’s four major fishing grounds, although the substantial overexploitation of fisheries has led to the collapse of many fish stocks, and to changes to spawning grounds in recent decades. Classifying fish eggs is an important way to monitor the recruitment process and identify the spawning sites of fish. However, the lack of a basis for morphological identification and difficulties in correctly identifying fish eggs based on morphological characteristics has limited scientific studies. In the present study, we identified fish eggs using molecular detection of cytochrome c oxidase subunit I and cytochrome b fragments. Ichthyoplankton surveys were conducted in the spring and late autumn–winter of 2020 in the eastern Beibu Gulf. Among the DNA extracted from the 873 chosen fish eggs, we successfully obtained 541 high-quality cytochrome c oxidase subunit I sequences and 41 high-quality cytochrome b sequences. We successfully identified 212 fish eggs (36.4%) from 32 species; 291 eggs (50.0%) showed ambiguous species delimitation, and 79 eggs (13.6%) could not be identified. Among the identified species, we found 25 species in spring and 25 species in late autumn–winter, out of which 18 species occurred in both seasons. We also obtained high resolution photographs of fish eggs at the species level for further morphological analysis and identification. The present study confirms the efficacy of using molecular methods to identify fish species from eggs and provides valuable information for protecting the spawning ground of economically valuable fish and for managing fishery resources.

Driving forces for recovery of forest vegetation after harvesting a subalpine oak forest in eastern Tibetan Plateau - Qinli Xiong; Lingjuan Li; Xiaojin Luo; Xingjin He; Lin Zhang; Kaiwen Pan; Chenggang Liu; Hui Sun (Environmental Science and Pollution Research, 2021)

Assemblage Structure of the Ichthyoplankton and Its Relationship With Environmental Factors in Spring and Autumn off the Pearl River Estuary - Gang Hou; Jinrun Wang; Limei Liu; Yanying Chen; Chuanhao Pan; Jianbin Lin; Hui Zhang (Frontiers in Marine Science, 2021)
Ichthyoplankton assemblages and their relationship with environmental variables are investigated in waters off the Pearl River Estuary in spring and autumn of 2019. Of 80 ichthyoplankton taxa identified using DNA barcode and morphological methods, 61 are identified to species. The most abundance families (Carangidae, Trichiuridae, Mullidae, and Scombridae) account for 61.34% of the horizontal total catch in spring, while Menidae and Carangidae are the most abundant families identified in autumn, accounting for 89.72% of the horizontal total catch. Cluster analysis identifies three species assemblages in spring, and four in autumn based on horizontal trawls. Relationships between assemblage structure and environmental variables ( in situ and remote sensed) are determined by canonical correspondence analysis. Ichthyoplankton assemblage structure appears to be strongly influenced by sea level anomalies, salinity, water depth, temperature at 10 m depth, and distance from shore. We demonstrate the efficacy of using DNA barcode to identify ichthyoplankton, and suggest how these data can be used to protect fish spawning grounds in waters off the Pearl River Estuary.

Application of the modified cytosine base-editing in the cultured cells of bama minipig - Jia-sheng Pan; Zi-sheng Lin; Jian-cong Wen; Jian-feng Guo; Xia-hui Wu; Ying-ying Liu; Wen-jun Lai; Qi-ying Liang; Yong-shi Xie; Yi-rou Chen; Yi-hong Chen; Ai-fen Yan; et al. (Biotechnology Letters, 2021)

Nitrogen‐induced acidification, not N‐nutrient, dominates suppressive N effects on arbuscular mycorrhizal fungi - Shang Pan; Yang Wang; Yunpeng Qiu; Dima Chen; Lin Zhang; Chenglong Ye; Hui Guo; Weixing Zhu; Aiqun Chen; Guohua Xu; Yi Zhang; Yongfei Bai; et al. (Global Change Biology, 2020)
Arbuscular mycorrhizal fungi (AMF) form symbiosis with most terrestrial plant roots, obtaining photosynthates in return for mineral nutrients. Ecological theories based on the economics of trading partnership predict that nutrient enrichment would suppress AMF. Experimental results from nitrogen (N) and phosphorus (P) additions, however, were highly variable, and the underlying mechanisms remain unclear. Here we show distinct AMF responses to soil N:P stoichiometry manipulations via gradients of long‐term N and P additions in a Mongolian steppe. A complementary experiment with an acid addition gradient was designed to help tease apart the effect of N‐induced acidification from N nutrient. AMF root colonization and extraradical fungal biomass progressively decreased along the P gradient under two distinct host plant species, suggesting a carbon (C)‐P tradeoff. In contrast, low to moderate N inputs increased both AMF parameters, corresponding to the increasing N:P ratio. Yet, high N inputs reduced AMF colonization and biomass, and the magnitudes of N‐led inhibition were similar to those under acid additions that induced comparable changes in soil pH. Structural equation modeling further showed that while soil N:P stoichiometry primarily controlled the effect of P addition on AMF, N‐induced soil acidity overtook the N:P stoichiometry under high N inputs and dominated the effects of reactive N on AMF. In addition, AMF community composition in roots was more dependent on host plants and unresponsive to changes in soil nutrients. We further proposed a comprehensive framework that integrates biological and geochemical effects of reactive N and P inputs on AMF. Together, these results indicate that while the C‐P tradeoff controls P suppression of AMF, N‐induced acidification dominates the N inhibition. Our findings suggest that incorporation of geochemical impacts of N and P inputs would facilitate modeling efforts to project mycorrhizal impact on plant interactions and soil C balance under future nutrient enrichment scenarios.

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Large paleo-rockslide induced by buckling failure at Jiasian in Southern Taiwan - Che-Ming Yang; Keng-Hao Kang; Shun-Hsing Yang; Kuo-Wei Li; Hui-Jung Wang; Yin-Tsan Lee; Kuei-Kun Lin; Yii-Wen Pan; Jyh-Jong Liao (Landslides, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Global buckling prevention of reduced-core-length buckling-restrained braces: theoretical and numerical investigations - Jing-Zhong Tong; Yan-Lin Guo; Wen-Hao Pan; Min-Hui Shen; Peng Zhou (Bulletin of Earthquake Engineering, 2020)

Tidal variability in the Hong Kong region - Adam T. Devlin; Jiayi Pan; Hui Lin (Ocean Science, 2019)
Mean sea level (MSL) is rising worldwide, and correlated changes in ocean tides are also occurring. This combination may influence future extreme sea levels, possibly increasing coastal inundation and nuisance flooding events in sensitive regions. Analyses of a set of tide gauges in Hong Kong reveal complex tidal behavior. Most prominent in the results are strong correlations of MSL variability to tidal variability over the 31-year period of 1986–2016; these tidal anomaly correlations (TACs) express the sensitivity of tidal amplitudes and phases (M2, S2, K1, O1) to MSL fluctuations and are widely observed across the Hong Kong region. At a few important harbor locations, time series of approximations of the parameter δ-HAT, computed from combinations of the major tidal constituents, are found to be highly sensitive to MSL variability, which may further increase local flood levels under future MSL rise. Other open-water locations in Hong Kong only show TACs for some individual tidal constituents but not for combined tidal amplitudes, suggesting that the dynamics in enclosed harbor areas may be partially frequency dependent and related to resonance or frictional changes. We also observe positive correlations of the fluctuations of diurnal (D1) tides to semidiurnal (D2) tides at most locations in the region, which may lead to further amplified tidal ranges under MSL. It is demonstrated here that tidal changes in the Hong Kong coastal waters may be important in combination with MSL rise in impacting future total water levels.

Effect of Partial Root-Zone Drying Irrigation (PRD) on the Gas Exchange and Antioxidant Enzymatic Activities in Alfalfa - Jing Zhang; Hui Xia Liu; Xiao Pan Pang; Cheng Yu; Qian Wang; Yu Pei Zhou; Li Guo Lin; Zheng Gang Guo (Journal of Soil Science and Plant Nutrition, 2019)

Impaired Hypothalamic Regulation of Sympathetic Outflow in Primary Hypertension - Jing-Jing Zhou; Hui-Jie Ma; Jian-Ying Shao; Hui-Lin Pan; De-Pei Li (Neuroscience Bulletin, 2019)

A refined model for lithosphere evolution beneath the decratonized northeastern North China Craton - A-Bing Lin; Jian-Ping Zheng; Qing Xiong; Sonja Aulbach; Jiang-Gu Lu; Shao-Kui Pan; Hong-Kun Dai; Hui Zhang (Contributions to Mineralogy and Petrology, 2019)

Composition and evolution of the lithospheric mantle beneath the interior of the South China Block: insights from trace elements and water contents of peridotite xenoliths - Hui Zhang; Jianping Zheng; Jianggu Lu; Shaokui Pan; Yi Zhao; Abing Lin; Lu Xiang (Contributions to Mineralogy and Petrology, 2018)

Correction to: Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbing Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

Heat stress alters genome-wide profiles of circular RNAs in Arabidopsis - Ting Pan; Xiuqiang Sun; Yangxuan Liu; Hui Li; Guangbin Deng; Honghui Lin; Songhu Wang (Plant Molecular Biology, 2018)

A quantitative method for risk assessment of agriculture due to climate change - Zhiqiang Dong; Zhihua Pan; Pingli An; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dong Wu; Jialin Wang; Dongliang Fan; et al. (Theoretical and Applied Climatology, 2018)

Association mapping analysis of fiber yield and quality traits in Upland cotton (Gossypium hirsutum L.) - Mulugeta Seyoum Ademe; Shoupu He; Zhaoe Pan; Junling Sun; Qinglian Wang; Hongde Qin; Jinhai Liu; Hui Liu; Jun Yang; Dongyong Xu; Jinlong Yang; Zhiying Ma; et al. (Molecular Genetics and Genomics, 2017)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Investigation of lead(II) uptake by Bacillus thuringiensis 016 - Zhi Chen; Xiaohong Pan; Hui Chen; Zhang Lin; Xiong Guan (World Journal of Microbiology and Biotechnology, 2015)

Investigation of Methylene Blue Biosorption and Biodegradation by Bacillus thuringiensis 016 - Zhi Chen; Hui Chen; Xiaohong Pan; Zhang Lin; Xiong Guan (Water, Air, & Soil Pollution, 2015)

Antimicrobial peptide GW-H1-induced apoptosis of human gastric cancer AGS cell line is enhanced by suppression of autophagy - Wei-Ru Pan; Yi-Lin Sophia Chen; Hui-Chen Hsu; Wei-Jung Chen (Molecular and Cellular Biochemistry, 2015)

Integrated assessment of China’s agricultural vulnerability to climate change: a multi-indicator approach - Yingchun Li; Wei Xiong; Wei Hu; Pam Berry; Hui Ju; Erda Lin; Wen Wang; Kuo Li; Jie Pan (Climatic Change, 2015)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Lack of association between let-7 binding site polymorphism rs712 and risk of nasopharyngeal carcinoma - Xin-Min Pan; Jing Jia; Xiao-Min Guo; Zhao-Hui Li; Zhen Zhang; Hao-Jie Qin; Guo-Hui Xu; Lin-Bo Gao (Familial Cancer, 2014)

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Moscatilin inhibits migration and metastasis of human breast cancer MDA-MB-231 cells through inhibition of Akt and Twist signaling pathway - Hui-Chen Pai; Li-Hsun Chang; Chieh-Yu Peng; Ya-Ling Chang; Chien-Chih Chen; Chien-Chang Shen; Che-Ming Teng; Shiow-Lin Pan (Journal of Molecular Medicine, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

New strategy for specific activation of recombinant microbial pro-transglutaminase by introducing an enterokinase cleavage site - Kun Wang; Bin Wang; Hui-Lin Yang; Li Pan (Biotechnology Letters, 2013)

Interactions of interleukin-12A and interleukin-12B polymorphisms on the risk of intracranial aneurysm - Li-Juan Li; Xin-Min Pan; Xiutian Sima; Zhao-Hui Li; Lu-Shun Zhang; Hong Sun; Yi Zhu; Wei-Bo Liang; Lin-Bo Gao; Lin Zhang (Molecular Biology Reports, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Calculation of the sensible heat flux of the global ocean using satellite data - Jiayi Pan; Hui Lin (International Journal of Remote Sensing, 2012)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

The proportions and variations of the light absorption coefficients of major ocean color components in the East China Sea - Hui Lei; Delu Pan; Yan Bai; Bangyi Tao; Jun Sun; Lin Zhang; Xuan Zhang (Acta Oceanologica Sinica, 2012)

Shallow water depth retrieval from space-borne SAR imagery - Kaiguo Fan; Weigen Huang; Hui Lin; Jiayi Pan; Bin Fu; Yanzhen Gu (Journal of Oceanography, 2011)

The effect of feed salinity on the biofouling dynamics of seawater desalination - Hui-Ling Yang; Jill R. Pan; Chihpin Huang; Justin Chun-Te Lin (Biofouling, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Cu(II): a “signaling molecule” of the mangrove endophyte Fusarium oxysporum ZZF51? - Jia-hui Pan; Yong-cheng Lin; Ni Tan; Yu-cheng Gu (BioMetals, 2010)

Denbinobin induces apoptosis by apoptosis-inducing factor releasing and DNA damage in human colorectal cancer HCT-116 cells - Tzu-Hsuan Chen; Shiow-Lin Pan; Jih-Hwa Guh; Chien-Chih Chen; Yao-Ting Huang; Hui-Chen Pai; Che-Ming Teng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Characterization of Antheraea pernyi nucleopolyhedrovirus p11 gene, a homologue of Autographa californica nucleopolyhedrovirus orf108 - Sheng-Lin Shi; Min-Hui Pan; Cheng Lu (Virus Genes, 2007)

Microsatellite polymorphism in promoter of heme oxygenase-1 gene is associated with susceptibility to coronary artery disease in type 2 diabetic patients - Ying-Hwa Chen; Shing-Jong Lin; Ming-Wei Lin; Hui-Ling Tsai; San-San Kuo; Jaw-Wen Chen; Min-Ji Charng; Tao-Cheng Wu; Lung-Ching Chen; Philip Ding; Wen-Harn Pan; Yuh-Shan Jou; et al. (Human Genetics, 2002)